PELATIHAN FUN LEARNING DENGAN MENGGUNAKAN KECERDASAN BUATAN PADA PEMBELAJARAN EDUKATIF UNTUK SISWA SISWI DI SMP MUHAMMADIYAH 29 SAWANGAN - Ilham Idfiana; Wahid Aldi Nugroho; Muhammad Akbar Chalil; Muhammad Suprihatin; Rizki Kurniandi; Muhammad Ilham Kurniawan; Irfan Saeful Bahri; Sudarno (Abdi Jurnal Publikasi, 2026)
This Community Service activity carries the theme “Fun Learning Training Using Artificial Intelligence in Educational Learning for Junior High School Students.” This program aims to provide an interactive learning experience by utilizing AI chatbots and other AI-based applications to support general learning. This training involves basic theory on AI, demonstrations on the use of chatbots for subjects, hands-on practice in the form of interactive quizzes and storytelling, to creative mini projects. Through this activity, it is hoped that students will be more motivated to learn, understand how to use AI wisely, and improve their digital literacy. Of the 29 participants divided into 6 groups, all activities—from creating short stories with AI chatbots, visualizing images, to creating songs. These results confirm that the use of AI in educational learning can provide an interactive, enjoyable, and productive learning experience, while also opening up new insights for teachers in integrating modern technology into the learning process.